Successful reconstruction of whole mitochondrial genomes from ancient Central America and Mexico. Issue 1 (December 2017) - Morales-Arce, Ana; Hofman, Courtney; Duggan, Ana; Benfer, Adam; Katzenberg, M.; McCafferty, Geoffrey; Warinner, Christina
Abstract The northern and southern peripheries of ancient Mesoamerica are poorly understood. There has been speculation over whether borderland cultures such as Greater Nicoya and Casas Grandes represent Mesoamerican outposts in the Isthmo-Colombian area and the Greater Southwest, respectively. Poor ancient DNA preservation in these regions challenged previous attempts to resolve these questions using conventional genetic techniques. We apply advanced in-solution mitogenome capture and high-throughput sequencing to fourteen dental samples obtained from the Greater Nicoya sites of Jícaro and La Cascabel in northwest Costa Rica (n = 9; A.D. 800–1250) and the Casas Grandes sites of Paquimé and Convento in northwest Mexico (n = 5; A.D. 1200–1450). Full mitogenome reconstruction was successful for three individuals from Jícaro and five individuals from Paquimé and Convento. The three Jícaro individuals belong to haplogroup B2d, a haplogroup found today only among Central American Chibchan-speakers. The five Paquimé and Convento individuals belong to haplogroups C1c1a, C1c5, B2f and B2a which, are found in contemporary populations in North America and Mesoamerica. We report the first successfully reconstructed ancient mitogenomes from Central America, and the first genetic evidence of ancestry affinity of the ancient inhabitants of Greater Nicoya and Casas Grandes with contemporary Isthmo-Columbian and Greater Southwest populations, respectively.